Feminist Traces of Memory Studies in Latin America and the Caribbean (KULT_online, 2024)
The book Memoria y Feminismos: Cuerpos, sentipensares y resistencias is a collective effort of different authors to contribute to the debates on memory in Latin America and the Caribbean. The texts reflect on corporality and political practices of memory. Across thirteen articles the authors deploy the postulates of corpo-politics and feminist standpoint theory as a theoretical framework. The volume presents a critical approach and questions the role of Eurocentric academia while giving insights into localized and experience-oriented research.